A lady's guide to mischief and murder - Freeman, Dianne, 1958- (Freeman, Dianne, 1958- Countess of Harleigh mystery, 2020)
A private family wedding at a bucolic Hampshire estate is threatened by the arrival of the Countess of Harleigh's socially ambitious mother and a series of accidents that are tied to the agenda of an unknown saboteur.